Covid-19 Global, Pandemic impact on World Economy - Muhammad Fahad Sattar,; Sehrish Khanum,; Ahsan Nawaz,; Muhammad Muzamal Ashfaq,; Muhammad Anas Khan,; Muhammad Jawad,; Waseem Ullah, (Technium Social Sciences Journal, 2020)
This exploratory study is carried out in April, 2020, when corona virus is spread all over the world and become Economic crisis 2020.The objective of this study is to answer some questions arise in mind, how many countries infected and reduce their economic activities? What are effective fiscal and monetary policies at international level to address the crisis? Is monetary and fiscal policy used as vaccine to prevent the world economy from crisis? It is a hot topic these days when world is facing this covid-19. Researcher get information from different website, international monetary fund(IMF), Organization of economic cooperation and development (OECD) Standard& poor’s, (S&P) rating agencies, and some past papers to explain the impact of Corona virus on world economy. Further explain the losses from one industry to another industry. And finally concluded that world economy is fighting with dual nature crisis. On one hand Death of million people from corona, other is fall down of economy. First challenge is to save the people from death, and secondly to save the world from economic crisis. But these two challenges are contradicted. If want to save people lives then implemented stay at home, social distancing policy, and shut down the country. But we can save our people live but economy fall down sharply because of shut down all businesses in the country. If save economic crisis then people should go out and work as usual, world economy will boost but soon we will lose million or billion of people live which also effect the fall down economy. Policy maker, doctors and health care manufacturer should sit together find ways which is benefits for both people live and save economic crisis.